The Effect of Lipopolysaccharide-Induced Experimental Bovine Mastitis on Clinical Parameters, Inflammatory Markers, and the Metabolome: A Kinetic Approach - Johnzon, Carl-Fredrik; Dahlberg, Josef; Gustafson, Ann-Marie; Waern, Ida; Moazzami, Ali A.; Östensson, Karin; Pejler, Gunnar (Frontiers in Immunology, 2018)
Mastitis is an inflammatory condition of the mammary tissue, and represents a major problem for the dairy industry worldwide. The present study was undertaken to study how experimentally induced acute bovine mastitis affects inflammatory parameters and changes in the metabolome. To this end we induced experimental mastitis in 9 cows by intramammary infusion of 100 µg purified Escherichia coli lipopolysaccharide (LPS) followed by kinetic assessments of cytokine responses (by ELISA), changes in the metabolome (assessed by NMR), clinical parameters (heat, local pain perception, redness, swelling, rectal temperature, clot formation and colour changes in the milk) and milk somatic cell counts, at several time points post LPS infusion. Intramammary LPS infusion induced clinical signs of mastitis, which started from 2 hours post infusion and had returned to normal levels within 24 to 72 hours. Milk changes were seen with a delay compared with the clinical signs, and persisted for a longer time. In parallel, induction of IL-6 and TNF-α were seen in milk, and there was also a transient elevation of plasma IL-6 whereas plasma TNF-α was not significantly elevated. In addition, a robust increase in CCL2 was seen in the milk of LPS-infused cows, whereas G-CSF, CXCL1 and histamine in milk were unaffected. By using a metabolomics approach, a transient increase of plasma lactose was seen in LPS-induced cows. In plasma, significant reductions in ketone bodies (3-hydroxybutyrate and acetoacetate) and decreased levels of short-chain fatty acids, known to be major products released from the gut microbiota, were observed after LPS infusion; a profound reduction of plasma citrate was also seen. Intramammary LPS infusion also caused major changes in the milk metabolome, although with a delay in comparison with plasma, including a reduction of lactose. We conclude that the LPS-induced acute mastitis rapidly affects the plasma metabolome and cytokine induction with similar kinetics as the development of the clinical signs, whereas the corresponding effects in milk occurred with a delay.